Using google location APIs to find an accurate criminal accident location - Irwan Padli Nasution, Muhammad; Samsudin, Samsudin (International Journal of Engineering and Technology, 2018)
Globalization has brought about a change in social behavior of society. The open access to information from the development and utilization of Information and Communication Technology has brought about a very significant change in the culture and behavior of society. Current-ly, Smartphone as a mobile-based communication tool has many benefits for use by the community. Various features contained in it so that an application can be developed for use by the public as a media reporting the location of the crime. Thus, the security forces will be assisted to obtain accurate information about the position where the crime occurred. One of the unique features of mobile applications is location awareness. To get an accurate location is necessary. Using Google Location APIs to get more accurate location. Applications like this do not exist in Indonesia, so it can be developed to help the police quickly get to the location of the case.Â